The familial history of hypertension influences the blood pressure response to the resistance exercise in normotensive men - Ivna Vidal Freire; Ana Angélica Leal Barbosa; Ícaro José Santos Ribeiro; Ludmila Schettino; Alinne Alves Oliveira; Alexander J. Koch; Marco Machado; Rafael Pereira (Asociación Española de Ciencias del Deporte, 2018)
Introduction: It is well known that familial or genetic heritage is closely associated to hypertension. Thus the present study aimed to investigate BP response to resistance exercise from young normotensive subjects with (WFHH) and without (WTFHH) familial history of hypertension (FHH). Material and Methods: Forty-nine healthy male, engaged in military service, were clinically examined. After anamneses volunteers were divided into two groups based on the FHH (mother and/or father). The groups were named: WFHH (n=22) and WTFHH (n=27). Volunteers performed three sets of 10 repetitions of unilateral knee extension at 50%, 75% and 100% of 10 repetition maximum (RM), with two-minute rest intervals between sets. Blood pressure measures were obtained at rest (PRE) and immediately after (POS) each exercise set. Result and Discussion: The results reveal that WFHH group exhibited greater SBP and PP response to resistance exercise at 50% of 10RM. These findings may indicate the presence of functional, and/or subclinical structural changes in young subjects with FHH, which are not clear at rest condition, but revealed during light resistance exercise.